2013
DOI: 10.1111/cmi.12177
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcineurin and actin dynamics in regulated secretion of microneme proteins inPlasmodium falciparummerozoites during erythrocyte invasion

Abstract: SummaryPlasmodium falciparum invades host erythrocytes by multiple invasion pathways. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…The requirement of calcineurin for the function of host receptor interactions involving PfRh and EBL molecules shows that parasite signal transduction is fundamental to a specific mechanism for host cell recognition by the parasite, independent of invasion ligand release from apical organelles. (Given our findings, a previous report that CsA and FK506 inhibit microneme exocytosis at high concentrations (Singh et al, 2014) might reflect the action of targets secondary to calcineurin.) Previously, the use of inhibitory antibodies showed that PfRh5 synergistically cooperates with the more variably expressed PfRh and EBL-family ligands to promote invasion (Williams et al, 2012), with a more recent study further providing evidence that PfRh5 acts downstream of other PfRh and EBL ligands (Weiss et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The requirement of calcineurin for the function of host receptor interactions involving PfRh and EBL molecules shows that parasite signal transduction is fundamental to a specific mechanism for host cell recognition by the parasite, independent of invasion ligand release from apical organelles. (Given our findings, a previous report that CsA and FK506 inhibit microneme exocytosis at high concentrations (Singh et al, 2014) might reflect the action of targets secondary to calcineurin.) Previously, the use of inhibitory antibodies showed that PfRh5 synergistically cooperates with the more variably expressed PfRh and EBL-family ligands to promote invasion (Williams et al, 2012), with a more recent study further providing evidence that PfRh5 acts downstream of other PfRh and EBL ligands (Weiss et al, 2015).…”
Section: Discussionsupporting
confidence: 77%
“…To study a possible function for Plasmodium calcineurin near the time of host cell invasion, we considered the drugs FK506 and cyclosporin A, which are each nanomolar inhibitors of physiological, mammalian calcineurin (Fruman et al, 1992). By contrast, both drugs are toxic to P. falciparum only in the micromolar range (Bell et al, 1994; Singh et al, 2014) (Figure S1A), and have been shown to act potently on parasite targets other than calcineurin (Bell et al, 2006). We found that FK506 and cyclosporin A strongly inhibit general parasite development at multiple stages of the intraerythrocytic cell cycle (Figure S1B), precluding their use for assessment of specific parasitic processes.…”
Section: Resultsmentioning
confidence: 99%
“…PP2B first garnered attention in apicomplexans because of their sensitivity to Cyclosporin A (CsA) and FK506 (Dobson et al, 1999), two immunosuppressants known to act through calcineurin inhibition in mammalian cells (Jun Liu et al, 1991). Both FK506 and CsA inhibit the secretion of microneme proteins in P. falciparum, suggesting a relationship between calcineurin with the effector(s) of Ca 21 -dependent microneme exocytosis (Singh et al, 2014). Similarly, CsA was shown to block T. gondii egress, which is also dependent on calcium dependent secretion and motility (Moudy et al, 2001).…”
Section: Pp2b Pp5 and Pp7mentioning
confidence: 99%
“…It appears that two PfRh proteins, PfRh1 and PfRh5, have distinct functions which are different from the others [15,16]. PfRh1 likely has a role immediately upstream of the alternative-pathway ligands, in signalling the release of micronemes containing EBA-175 [16], a process which is dependent on calcium [17]. While the alternative-pathway EBA and PfRh ligands bind to different erythrocyte receptors, studies with gene knockout parasites, in combination with mutant erythrocytes deficient in particular receptors, have shown that increased expression of some EBAs and PfRhs can functionally compensate for the lack of another [18,19,20].…”
Section: Introductionmentioning
confidence: 99%